Analisis Ekonomi Politik Neoklasik dalam Pembangunan Infrastruktur di Indonesia - Siti Safina; Eli Apud Saepudin; Aulia Shafa Damayanti; Leni Rahma Yani; Lutfiana Edista; , Septia Cahyani (UNIVERSITAS SERAMBI MEKKAH, 2024)
The purpose of this research is to understand that infrastructure development in Indonesia is the main focus of the government in improving economic growth and public welfare. Neoclassical political economy analysis offers an important perspective to understand how political and economic actors interact in the infrastructure development process. The research method of neoclassical political economy analysis in the perspective of infrastructure development in Indonesia uses a qualitative descriptive method. In this research, the focus of the research is the political economy process of distributing the development fund budget. Neoclassical political economy analysis offers an important perspective to understand the complexity of infrastructure development in Indonesia. By understanding the roles and interests of the actors involved, as well as the important issues faced, this analysis can assist in formulating more effective and sustainable infrastructure development policies and strategies. Infrastructure development priorities are determined by market mechanisms, i.e. projects that are considered economically profitable.